UJI KELAYAKAN MEDIA PERMAINAN TRUTH OR DARE UNTUK MENINGKATKAN PERILAKU ASERTIF SISWA KELAS XI SMK BINA PRESTASI BANGSA - Ridwan Wahid Sawaludin; Wahyu Hidayat; Resti Okta Sari (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This study aims to determine the feasibility test of the truth or dare card game media to increase students' assertive behavior. This type of research uses Research and Development (R&D) Borg and Gall research methods. The sample in this study were students of class XI SMK Bina Prestasi Bangsa as many as 30 students. Data processing using Microsoft Excel application. The results of the feasibility test that have been carried out on media experts, material experts, practitioners, and students show an average score of 93.12%. The developed game media has an influence on the average percentage of students' assertive behavior by 12.94% from 61.65% initially to 74.59%. Thus, it shows that the truth or dare game media has had a positive influence and has fulfilled the aspect of product effectiveness. The conclusions in this study are: 1) the truth or dare game media in group guidance to improve assertive behavior is very feasible to use, and 2) truth or dare game media in group guidance is effectively used to improve students' assertive behavior.